Business Sustainability Transformation in Creative Culinary SMEs in Surakarta City - Utami, Indah Wahyu; Hastuti, Indra; Ardiyanto, Marta; Saputri, Lisa Nur Savira Dewi; Adirangga, Ihsan Kandung (MultiTech Publisher, 2025)
The creative industry is one of the strategic sectors that can significantly drive national economic growth. In this context, Micro, Small, and Medium Enterprises (MSMEs) operating in the creative industry, particularly the culinary sector, demonstrate great potential in creating economic value while also opening up employment opportunities. This study aims to develop a business sustainability model for creative industry MSMEs through business diversification and the implementation of environmentally friendly human resource management practices. The research focuses on culinary sector MSMEs in the city of Surakarta as a representation of the rapidly growing and highly competitive creative industry. Data collection methods include literature review, surveys, and interviews with culinary sector MSMEs in the city of Surakarta. The results of this study are expected to contribute theoretically to the development of a business sustainability model and serve as a practical guide for SMEs in enhancing the resilience and sustainability of their businesses amid the dynamic, competitive, and sustainable business environment